A review of daylighting and visual comfort in green building rating tools / Fazidah Hanim Husain ... [et al.] - Husain, Fazidah Hanim; Abdul Aziz, Azhan; Yuhaniz, Mayamin; Abas, Salahuddin Abdul Hakeem; Sheikh Ahmad, Sabarinah (2021)
One of the main components of interior space is lighting. Daylight offers a high-quality indoor environment that provides the required illumination for visual comfort. Well-designed architecture allows natural light to be transmitted, provides view, reduces heat, and eliminates glare in order to provide a work atmosphere that is conducive. Lack of understanding at the early stage of design and poor site consideration will produce high-energy buildings that encourage the usage of electrical lighting. A report from the Building Sector Energy Efficiency Project (BSEEP) stated that energy waste increased 50% because of lack of passive design knowledge. Post occupancy evaluation of GBI rated buildings show glare and employee discomfort occurred in office environment. This research is conducted to identify the score reading and weightage of daylighting and visual comfort in green building rating tools. The study provides an overview on daylighting-related measures in the certification of the commonly used rating tools worldwide such as LEED, BREEAM, CASBEE, SB TOOL, GREENMARK, NZ GREEN STAR, and GBI specifically in office buildings which were comparatively assessed and analysed. This comparison allows researcher to identify the score reading of the daylight performance and visual comfort that fall under the category of Energy and IEQ to highlight the weightage and importance of daylight and visual comfort from the perspective of green building. The analysis shows that the score readings between the rating tools on both categories vary and are not homogeneous, but are based according to the locality, climate, and the region.